Karakteristik Campuran AC-BC Menggunakan Batu Sungai Salo Pattejang Kecamatan Bungoro Kabupaten Pangkep - Dicky Josua Milenio Ambarura; Alpius; Elizabeth (Paulus Civil Engineering Journal, 2021)
Transportation infrastructure in the form of roads is one of the elements that is quite important in the development of an area that is experiencing very rapid development. Therefore, in the construction of road pavements, the best possible aggregate is obtained from the surrounding location which should be utilized as much as possible for the construction of road pavements. This study aims to determine the characteristics of the AC-BC mixture using the Sallo Patttejang river rock, Bungoro District, Pangkep Regency, to determine the composition of the AC-BC mixture and to determine the Marshall characteristics, the remaining Marshall stability in the AC-BC mixture. This research was conducted using the Marshall Method. Based on the results of the study, it can be seen that the KAO value is at 6% asphalt content, and the Stability value at KAO is 1544.13 Kg, VIM is 4.16%, flow is 2.50 mm, VMA is 17.21%, and VFB by 75.82%. These results indicate that all the characteristic parameters of the AC-BC mixture, namely stability, flow, VIM, VMA, and VFB all meet the General Specifications of Highways 2018.